Structural geology of rocks and regions - Davis, George H. | Reynolds, Stephen J. (Canada | CANADA John Wiley & SonS / Canada, 1996)
Structural geology of rocks and regions, he wanted to emphasize that the human adventure of learning comes from doing and that new insight springs from careful detailed examination of field relationship vieewd at all scale from rocks to regions
Sin Especificar
Keywords: Geología estructural